Factors Influencing the Effectiveness of Supply Chain Traceability System Implementation for Shark and Ray Products in Pahang, Malaysia: Insights from Key Informant Interviews - Roba’a Yusof,; Ahmad Shuib,; Sridar Ramachandran,; Ahmad Ali,; Illisriyani Ismail, (International Journal of Business and Society, 2022)
The objective of this study is to obtain experts’ opinions in identifying factors influencing the implementation of supply chain traceability for shark and ray products in Pahang, Malaysia. The information was obtained through structured key informant interviews (KIIs), which were conducted one-to-one and face-to-face with relevant experts from government agencies and Malaysia’s National Plan of Action (NPOA-Shark) committee members. From the text discourse analysis, the study has identified seven indicators that need to be improved and explored before developing the full implementation of the supply chain traceability system in Pahang. The indicators are as follows: (i) policy and strategic management; (ii) acts and regulations; (iii) shark and ray resources; (iv) manpower and capability; (v) infrastructure and management information system; (vi) collaboration efforts; and (vii) buy-ins from stakeholders. It is recommended that the government reviews the current policy, acts, regulations, and strategic initiatives to increase the commitment from all relevant stakeholders to ensure sustainable utilisation of shark and ray species.